The scalpel and the ledger: Finance, medicine and the making of a professional life in Ireland, India and Britain, 1888-1921 - Daniel Cassidy; Kieran Fitzpatrick (The European Association for Banking and Financial History (EABH), 2022)
By the time of his death in September 1921, Peter Johnstone Freyer was an extremely wealthy man. After an education at Queen's College Galway, his medical career had been defined by colonial service in India, and the establishment of a successful surgery and consultancy on London's Harley Street. In public, these hallmarks of his career led to him being described by his contemporaries as amongst medicine's most prominent figures, and as a 'great surgeon' by newspapers the length of and breadth of the United Kingdom on the occasion of his death. However, his private papers show that his medical practice was only responsible for a small part of his material success; two-thirds of his wealth was derived from his skill, exercised in private, as an investor in financial markets. By establishing his history as an investor, and comparing it to his public profile in medicine, this paper traces the social and cultural histories of professional identity in late-Victorian and Edwardian London. Over the course of its arc, it demonstrates how medicine's public significance in this period was part of a broader, middle-class, professional culture concerned with the accrual of 'virtual' wealth, the construction of advantageous social networks, and the tapping of capital in multiple forms. In sum, Freyer's career reflects the symbolic meaning of publicly wielding a scalpel, whilst privately managing a portfolio of financial ledgers.
Keywords: G41; N2; N3; 330; Financial markets; investment; risk